Portfolio preferences of foreign institutional investors - Aggarwal, Reena; Klapper, Leora; Wysocki, Peter D. (Journal of Banking & Finance, 2005)
This paper examines the investment allocation choices of actively-managed US mutual funds in emerging market equities after the market crises of the 1990s. We analyze both country- and firm-level disclosure and institutional policies that influence mutual funds’ allocation choices relative to major stock market indices. At the country level, we find that US funds invest more in open emerging markets with stronger accounting standards, shareholder rights, and legal frameworks. At the firm level, US funds are found to invest more in firms that adopt discretionary policies such as greater accounting transparency and the issuance of an ADR. Our results suggest that steps can be taken both at the country and the firm level to create an environment conducive to foreign institutional investment.